Different immunological characteristics of asymptomatic and symptomatic COVID-19 patients without vaccination in the acute and convalescence stages - Li Li; Xin Zhang; Huimin Yan; Muwei Dai; Huixia Gao; Yuling Wang; Ping Jiang; Erhei Dai (PeerJ)
The immune status of Coronavirus disease 2019 (COVID-19) patients in different stages of infection remains difficult to determine. In this study, we performed high-throughput single-cell mass cytometry on peripheral blood samples from 10 COVID-19 patients and four healthy donors to analyze their immune status at acute and convalescence phases. During the acute stage, the proportion of neutrophils increased significantly while natural killer (NK) cells decreased. In contrast, during the convalescence phase, the proportion of plasma cells decreased from the acute stage of disease onset and was lower than normal. The proportions of B, mast and plasma cell subsets decreased significantly with the process of disease recovery. Further analysis of the subsets of major immune cell types in COVID-19 patients with different clinical presentations in different stages showed that in the acute stages of disease progression, the T helper cell 1 (Th1), IgD+ B and neutrophil subsets increased in COVID-19 patients, especially in symptomatic patients, while the central memory CD4+T cells (CD4 TCM), mucosa-associated invariant T (MAIT) and NK cell subsets decreased significantly, especially in symptomatic patients. Then CD4 TCM and MAIT returned to normal levels at the recovery phase. Dynamic assessment displayed that the immune imbalance at the onset of COVID-19 could be corrected during recovery. Our study provides additional information on the immune status of COVID-19 patients with different clinical manifestations in different stages. These findings may provide new insights into COVID-19 immunotherapy and immune intervention.